2009
DOI: 10.1007/s11243-009-9222-z
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and biological activities of water-soluble nickel(II) and copper(II) complexes of a Schiff-base derived from paeonol

Abstract: Water-soluble Ni(II) and Cu(II) complexes of a flexible Schiff-base ligand have been synthesized, and the Ni(II) complex was characterized by X-ray crystallography. The interactions of the two complexes with calf thymus DNA were investigated by spectroscopic and viscosity measurements in water. The results suggest that the two complexes bind to DNA within the groove. Antioxidant experiments against OH • and O 2 -• show that these two complexes have excellent ability to scavenge O 2 -• , and the Cu(II) complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The researches of modern medicine verified that paeonol possesses other pharmacological activities, such as antiinflammation, anti-oxidation, sedative, acaricide, antiproliferation and apoptosis in cancer cell, immunoregulation and antimicrobial [3][4][5][6]. Although alarge number of studies about paeonol have been done in the lastdecades of years, the reports about its derivatives have only afew [1,2,7,8]. In this paper we report on anovel Schiff base derived from paeonol its preparation and its crystal structure.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The researches of modern medicine verified that paeonol possesses other pharmacological activities, such as antiinflammation, anti-oxidation, sedative, acaricide, antiproliferation and apoptosis in cancer cell, immunoregulation and antimicrobial [3][4][5][6]. Although alarge number of studies about paeonol have been done in the lastdecades of years, the reports about its derivatives have only afew [1,2,7,8]. In this paper we report on anovel Schiff base derived from paeonol its preparation and its crystal structure.…”
Section: Discussionmentioning
confidence: 94%
“…It has been used as antifebrile and analgesic for thousand years in Chinese [1,2]. The researches of modern medicine verified that paeonol possesses other pharmacological activities, such as antiinflammation, anti-oxidation, sedative, acaricide, antiproliferation and apoptosis in cancer cell, immunoregulation and antimicrobial [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Although al arge number of studies on paeonolhavebeendoneinrecentyears, reports about its derivatives are only afew [4][5][6]. This paperreports anew paeonolbased Schiff base andits crystalstructure.The titlecompoundcrystallizes with one molecule in the asymmetric unit.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In recent years, metal complexes of Schiff bases have attracted considerable attention due to their remarkable biological activity, such as antifungal, antibacterial and antitumor property. [7][8][9] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have interesting biological activity. [9][10][11][12] Furthermore, cobalt complexes in its varied oxidation states have become a central theme of current research because of their potentially useful properties in the realm of relevant scientific and technological fields.…”
Section: Introductionmentioning
confidence: 99%